Predictive values of anti-cyclic citrullinated peptide antibodies and rheumatoid factor in relation to serological aspects of the ACR/EULAR 2010 classification criteria for rheumatoid arthritis. (2nd January 2020) - Tenstad, HB; Nilsson, AC; Dellgren, CD; Lindegaard, HM; Rubin, KH; Lillevang, ST
Abstract : Objective : In this retrospective population-based register study, we wanted to determine the positive predictive values (PPVs) of immunoglobulin M rheumatoid factor (IgM RF) and anti-citrullinated protein antibodies (ACPAs) at 3 × upper normal limit (UNL), since they are weighted equally in the American College of Rheumatology (ACR)/ European League Against Rheumatism (EULAR) 2010 criteria for rheumatoid arthritis (RA). Methods : Test results, ordering unit, test date, and patient social security number were collected from the Department of Clinical Immunology at Odense University Hospital from 2007 to 2016 and merged with patient diagnosis from the Danish National Patient Registry. Results : The PPV of IgM RF at 3 × UNL was 14%, compared to a PPV of 43% for ACPAs at 3 × UNL. Conclusion : The PPV of ACPAs is higher than the PPV of IgM RF at 3 × UNL. These findings are not reflected in the ACR/EULAR 2010 classification criteria for RA.